Dynamic resistance and total loss in a three-tape REBCO stack carrying DC currents in perpendicular AC magnetic fields at 77 K. (8th February 2022) - Sun, Yueming; Fang, Jin; Sidorov, Gennady; Badcock, Rodney A; Long, Nicholas J; Jiang, Zhenan
Abstract: In many high-temperature superconducting (HTS) applications, HTS-coated conductors carry a DC current under an external AC magnetic field. In such operating conditions, dynamic resistance will occur when the traversing magnetic flux across the HTS conductors. Consequently, AC loss within the superconductors is composed of the dynamic loss component arising from dynamic resistance and the magnetization loss component due to the AC external magnetic field. This AC loss is one of the critical issues for HTS applications, such as persistent current switches, flux pumps, and rotating machines. In this work, the dynamic resistance and the total loss in a three-tape HTS coated conductor stack were measured at 77 K under perpendicular AC magnetic fields up to 80 mT and DC currents ( I dc ) up to the critical current ( I c ). The stack was assembled from three serial-connected 4 mm wide Superpower wires. The measured dynamic resistance results for the stack were well supported by the results from 2D H -formulation finite element modelling (FEM) and broadly agree with the analytical values for stacks. The FEM analysis shows asymmetric transport DC current profiles in the central region of the superconductor. We attribute the result to the superposition of DC currents and the induced subcritical currents which explains why the measured magnetization loss values increase with DC current levels at low magnetic field. The onset of dynamic loss for the stack for low i ( I dc / I c ) values is much slower when compared to that of the single tape and hence the contribution of the dynamic loss component to the total loss in the stack is much smaller than that of the single tape. Dynamic loss in the stack becomes comparable to the magnetization loss at i = 0.5 and becomes greater than the magnetization loss at i = 0.7. Both magnetization loss and dynamic loss in the stack are smaller than those of the single tape due to shielding effects. The difference between the Q total behaviours in the stack and single tape is due to the variation of the penetration depths of the stack and single tape at the different magnetic field amplitudes.